A study of phase separation processes in presence of dislocations in binary systems subjected to irradiation - Kharchenko, D.O.; Schokotova, O.M.; Bashtova, A.I.; Lysenko, I.O. (Condensed Matter Physics, 2015)
Dislocation-assisted phase separation processes in binary systems subjected to irradiation effect are studied analytically and numerically. Irradiation is described by athermal atomic mixing in the form of ballistic flux with spatially correlated stochastic contribution. While studying the dynamics of domain size growth we have shown that the dislocation mechanism of phase decomposition delays the ordering processes. It is found that spatial correlations of the ballistic flux noise cause segregation of dislocation cores in the vicinity of interfaces effectively decreasing the interface width. A competition between regular and stochastic components of the ballistic flux is discussed. Проведено дослiдження процесiв фазового розшарування за дислокацiйним механiзмом в бiнарних системах, пiдданих дiї опромiнення. Опромiнення описується атермiчним перемiшуванням атомiв, за рахунок уведення балiстичного потоку, що має просторово-скорельовану стохастичну складову. При вивченнi динамiки росту доменiв показано, що дислокацiйний механiзм уповiльнює процес упорядкування.
Встановлено, що просторовi кореляцiї шуму балiстичного потоку стимулюють сегрегацiю ядер дислокацiй в околi мiжфазних границь, ефективно зменшуючи ширину мiжфазного шару. Розглянуто конкуренцiю мiж регулярною та стохастичною компонентами балiстичного потоку.